12-h clock regulation of genetic information flow by XBP1s - Pan, Yinghong; Ballance, Heather; Meng, Huan; Gonzalez, Naomi; Kim, Sam-Moon; Abdurehman, Leymaan; York, Brian; Chen, Xi; Schnytzer, Yisrael; Levy, Oren; Dacso, Clifford C.; McClung, Colleen A.; et al. (PLOS Biology, 2020)
Distinct from the well-known 24-hour circadian clock, this study shows that the mammalian 12-hour clock upregulates genetic information flow capacity during the two "rush hours" (dawn and dusk) in a manner dependent on the transcription factor XBP1s.